Person-Organization Fit and Psychological Safety on Affective Commitment through Meaningful Work among University Lecturers - Nova Arestia; Lianto Lianto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Affective commitment is crucial for sustaining lecturers’ engagement and institutional loyalty in higher education. This study examines how person-organization fit and psychological safety shape affective commitment among university lecturers, with meaningful work proposed as a mediating mechanism. Using a quantitative approach, survey data from 74 lecturers at a private university in Indonesia were analyzed through Partial Least Squares Structural Equation Modeling. The results show that person–organization fit and psychological safety positively and significantly influence meaningful work and affective commitment. Meaningful work also has a significant positive effect on affective commitment. However, the indirect effect of person-organization fit on affective commitment through meaningful work was positive but statistically insignificant, while the indirect effect of psychological safety through meaningful work was also not significant, indicating that meaningful work did not mediate either relationship. These findings suggest that lecturers’ affective commitment is shaped primarily through direct value alignment and supportive interpersonal climates rather than indirect meaning-making mechanisms. The study contributes to organizational behavior literature by clarifying the limited mediating role of meaningful work in academic settings and implies that universities should strengthen institutional value congruence and psychologically safe work environments to enhance lecturers’ commitment.